Diversification of LytM Protein Functions in Polar Elongation and Cell Division of Agrobacterium tumefaciens - Figueroa-Cuilan, Wanda M.; Randich, Amelia M.; Dunn, Caroline M.; Santiago-Collazo, Gustavo; Yowell, Andrew; Brown, Pamela J. B. (Frontiers in Microbiology, 2021)
LytM-domain containing proteins are LAS peptidases known to play diverse roles throughout the bacterial cell cycle through direct or indirect hydrolysis of the bacterial cell wall. A subset of the LytM factors are catalytically inactive but regulate the activity of other cell wall hydrolases and are classically described as cell separation factors NlpD and EnvC. Here, we explore the function of four LytM factors in the alphaproteobacterial plant pathogen Agrobacterium tumefaciens. An LmdC ortholog (Atu1832) and a MepM ortholog (Atu4178) are predicted to be catalytically active. While Atu1832 does not have an obvious function in cell growth or division, Atu4178 is essential for polar growth and likely functions as a space-making endopeptidase that cleaves amide bonds in the peptidoglycan cell wall during elongation. The remaining LytM factors are degenerate EnvC and NlpD orthologs. Absence of these proteins results in striking phenotypes indicative of misregulation of cell division and growth pole establishment. The deletion of an amidase, AmiC, closely phenocopies the deletion of envC suggesting that EnvC is a regulator of AmiC activity. The NlpD ortholog DipM is unprecedently essential for viability and depletion results in the misregulation of early stages of cell division, contrasting with the canonical view of DipM as a cell separation factor. Finally, we make the surprising observation that absence of AmiC relieves the toxicity induced by dipM overexpression. Together, these results suggest EnvC and DipM may function as regulatory hubs with multiple partners to promote proper cell division and establishment of polarity.